Left posterior prefrontal regions support domain‐general executive processes needed for both reading and math. Issue 3 (8th February 2020) - Wang, Kai; Banich, Marie T.; Reineberg, Andrew E.; Leopold, Daniel R.; Willcutt, Erik G.; Cutting, Laurie E.; Del Tufo, Stephanie N.; Thompson, Lee A.; Opfer, John; Kanayet, Frank J.; Lu, Zhong‐Lin; Petrill, Stephen A.
Abstract : Substantial evidence has suggested that reading and math are supported by executive processes (EP). However, to date little is known about which portion of the neural system underpinning domain‐general executive skills works to support reading and math. In this study, we aimed to answer this question using fMRI via two complementary approaches. First, imaging data were acquired whilst a sample of 231 adolescents performed each of three separate tasks designed to assess reading comprehension, numerical magnitude estimation, and EP in working memory (WM), respectively. With careful task designs and conjunction analyses, we were able to isolate cross‐domain brain activity specifically related to EP, as opposed to lower‐level domain‐general processes (e.g., visual processing). Second, the meta‐analytic tool Neurosynth was used to independently identify brain regions involved reading, math, and EP. Using a combination of forward and reverse statistical inference and conjunction analyses, we again isolated brain regions specifically supporting domain‐general EP. Results from both approaches yielded overlapping activation for reading, math, and EP in the left ventrolateral prefrontal cortex, left inferior frontal junction, and left precentral gyrus. This pattern suggests that posterior regions of the prefrontal cortex, rather than more central regions such as mid‐DLPFC, play a leading role in supporting domain‐general EP utilized by both reading and math.